2014
DOI: 10.1016/j.neuroimage.2014.06.050
|View full text |Cite
|
Sign up to set email alerts
|

The reorganization of corticomuscular coherence during a transition between sensorimotor states

Abstract: Recent research suggests that neural oscillations in di↵erent frequency bands support distinct and sometimes parallel processing streams in neural circuits. Studies of the neural dynamics of human motor control have primarily focused on oscillations in the beta band (15 30 Hz). During sustained muscle contractions, corticomuscular coherence is mainly present in the beta band, while coherence in the alpha (8 12 Hz) and gamma (30 80 Hz) bands has not been consistently found. Here we test the hypothesis that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 71 publications
8
64
0
Order By: Relevance
“…In a previous study we showed that cortico-muscular coherence revealed synchronization in the alpha and gamma band only when participants made an overshoot when reaching the second target (Mehrkanoon et al, 2014b). We interpreted this dual-band synchronization as the afferent and efferent processes involved in parsing prediction errors and generating new motor predictions.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In a previous study we showed that cortico-muscular coherence revealed synchronization in the alpha and gamma band only when participants made an overshoot when reaching the second target (Mehrkanoon et al, 2014b). We interpreted this dual-band synchronization as the afferent and efferent processes involved in parsing prediction errors and generating new motor predictions.…”
Section: Discussionmentioning
confidence: 58%
“…For motor skill acquisition, we used a simple motor task in which participants were required to make a transition between two force levels as fast and accurately as possible. In a previous study we have shown a reorganization in corticomuscular coherence when participants make an overshoot when reaching the second target (Mehrkanoon et al, 2014b). Here we investigated how movement accuracy changes during a single session of motor training and compared cortico-cortical and cortico-cerebellar coherence during resting-state pre and post motor training.…”
Section: Experimental Designmentioning
confidence: 84%
“…This means that large-amplitude events occur by chance more often than expected for an exponential distribution because they are drawn from a heavier right hand tail. Although the deviation of the beta rhythm from a unimodal exponential PDF is less spectacular than alpha, the functional significance of beta oscillations to human motor output in health [16,17] and disease [18] underlines the importance of identifying generative mechanisms. Fisher-Tippett heavy tailed distributions are typical of highly-correlated complex systems, where the core assumptions of independence for Gaussian fluctuations are violated [19].…”
Section: Heavy-tailed Beta Rhythmsmentioning
confidence: 99%
“…High-frequency CMC becomes prominent during tasks involving strong (Mima et al, 1999) or dynamically modulated contractions (Brown et al, 1998; Omlor et al, 2007). Interestingly, CMC in alpha and gamma frequency bands appears also to be related to the reorganization of corticomuscular interactions during transitions between sensorimotor states (Mehrkanoon et al, 2014). In this specific study, gamma and alpha activities play a bilateral dual-band synchrony role presumably joining motor (descending, gamma) and sensory (ascending, alpha) processing during error corrections.…”
Section: Discussionmentioning
confidence: 99%